Double‐lung versus heart‐lung transplantation for precapillary pulmonary arterial hypertension: a 24‐year single‐center retrospective study. (5th March 2019) - Brouckaert, Janne; Verleden, Stijn E.; Verbelen, Tom; Coosemans, Willy; Decaluwé, Herbert; De Leyn, Paul; Depypere, Lieven; Nafteux, Philippe; Van Veer, Hans; Meyns, Bart; Rega, Filip; Van De Velde, Marc; et al.
Summary: Transplant type for end‐stage pulmonary vascular disease remains debatable. We compared recipient outcome after heart‐lung (HLT) versus double‐lung (DLT) transplantation. Single‐center analysis (38 HLT–30 DLT; 1991–2014) for different causes of precapillary pulmonary hypertension (PH): idiopathic (22); heritable (two); drug‐induced (nine); hepato‐portal (one); connective tissue disease (four); congenital heart disease (CHD) (24); chronic thromboembolic PH (six). HLT decreased from 91.7% [1991–1995] to 21.4% [2010–2014]. Re‐intervention for bleeding was higher after HLT; ( P  = 0.06) while primary graft dysfunction grades 2 and 3 occurred more after DLT; ( P  < 0.0001). Graft survival at 90 days, 1, 5, 10, and 15 years was 93%, 83%, 70%, 47%, and 35% for DLT vs. 82%, 74%, 61%, 48%, and 30% for HLT, respectively (log‐rank P  =   0.89). Graft survival improved over time: 100%, 93%, 87%, 72%, and 72% in [2010–2014] vs. 75%, 58%, 42%, 33%, and 33% in [1991–1995], respectively; P  = 0.03. No difference in chronic lung allograft dysfunction (CLAD)‐free survival was observed: 80% & 28% for DLT vs. 75% & 28% for HLT after 5 and 10 years, respectively; P  =   0.49. Primary graft dysfunction in PH patients was lower after HLT compared to DLT. Nonetheless, overall graft and CLAD‐free survival were comparable and improved over time with growing experience. DLT remains our preferred procedure for all forms of precapillary PH, except in patients with complex CHD.